The rank estimate of the commercial potential of intellectual technologies - Kosenko, Alexandra; Pererva, P. G. (Academic Society of Michal Baludansky, 2015)
In the article methodical approach to ranking the technologies created on the basis of intellectual property. The basis for the ranking is based on the desirability function Harrington, which is defined in the range from "0" to "1" and can be used as a dimensionless scale for assessing the levels of various parameters of the objects. The practical mechanism of action of the method relative assessment of the level of commercial potential of a number of alternative intelligent technology is considered on the example of technological process of manufacturing of rotor asynchronous motors. As an alternative technology products 8 discusses options of technologies of manufacturing of rotor asynchronous motor developed in Ukraine (5 technologies), Russia (two technologies) and Kazakhstan (one technology). The authors developed a methodology of ranking technologies, which includes 7 stages. In the first stage identifies technology-competitors and gathering information about their most important options. In the second stage, the calculated value of the reduced level of commercial potential of technologies for the boundary values of desirability function. In the third stage examines the values of indicators of alternative technologies, the characteristics of their consumption, the specific needs of consumers. In the fourth stage are the calculations of the coefficients of the approximating equations for each of the indicators that Express the analytical dependence between the summary value of the commercial potential and actual parameter value of each technology. At the fifth stage of the calculations the values of the combined commercial potential for all alternative technologies that are investigated. In the sixth stage, in accordance with the recommendations of the desirability function set rating values for each indicator of alternative technologies. The seventh stage is determined by the total value of commercial potential (generalized function of desirability Harrington) smart technologies that are compared. The authors have proved that the final result of the calculation by the proposed method largely depends on the number of parameters of the alternative technologies considered. The more parameters of the technologies considered, the more accurate top rated technology reproduces the specific conditions of consumption of a specific enterprise. But to a certain extent, reduced the assessment of scientific value and of progressive technologies, which are offset to additional, less important factors.

В статті розроблено методичний підхід до ранжування технологій, створених на основі об’єктів інтелектуальної власності. В основу ранжування покладено функцію бажаності Харрінгтона, яка визначена в інтервалі від «0» до «1» і може бути використана в якості безрозмірної шкали для оцінки рівнів параметрів різних об'єктів. Механізм практичної дії методу відносної оцінки рівня комерційного потенціалу низки альтернативних інтелектуальних технологій розглянуто на прикладі технологічного процесу виготовлення ротора асинхронних двигунів. В якості альтернативних технологічних продуктів розглядаються 8 варіантів технологій виготовлення ротора асинхронного двигуна, розроблених в Україні (5 технологій), Росії (дві технологій) та Казахстану (одна технологія). Авторами розроблена методика ранжування технологій, яка включає в себе 7 стадій. На першій стадії виявляються технології-конкуренти і проводиться збір інформації про їх найважливіші параметри. На другій стадії розраховуються значення приведеного рівня комерційного потенціалу технологій для граничних значень функції бажаності. На третій стадії аналізуються значення показників альтернативних технологій, особливостей їх споживання, специфічних запитів споживачів. На четвертій стадії здійснюються розрахунки коефіцієнтів апроксимуючих рівнянь для кожного з показників, що виражають аналітичну залежність між зведеними значенням комерційного потенціалу і фактичним значенням параметра кожної технології. На п’ятій стадії проводяться розрахунки значення зведеного комерційного потенціалу для всіх альтернативних технологій, які досліджуються. На шостій стадії згідно з рекомендаціями функції бажаності встановлюються рейтингові значення по кожному показнику альтернативних технологій. На сьомій стадії визначається зведене значення комерційного потенціалу (узагальнена функція бажаності Харрінгтона) інтелектуальних технологій, що порівнюються. Авторами доведено, що кінцевий результат розрахунку за пропонованою методикою, в значній мірі залежить від кількості параметрів альтернативних технологій, які розглядаються. Чим більше параметрів технологій розглядається, тим точніше краща за рейтингом технологія відтворює специфіку умов її споживання на конкретному підприємстві. Але при цьому в певній мірі зменшується оцінка наукової значущості і прогресивності технології, які нівелюються додатковими показниками.
Рангова оцінка комерційного потенціалу інтелектуальних технологій
Keywords: technology; intellectual property; indicators; commercial potential; ranking; технологія; власність інтелектуальна; показники; потенціал комерційний; ранжування